KARAKTERISTIK HABITAT TEMPAT BERTELUR PENYU SISIK (Eretmochelys imbricata ) DI TAMAN WISATA ALAM TANJUNG KELUANG KECAMATAN KUMAI KALIMANTAN TENGAH - Karim, Muhamad Nur; Rifanjani, Slamet; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2019)
This research aimed to discover the characteristics of hawksbill turtle egg-laying place (Eretmochelys imbricata) in the Tanjung Keluang Nature Park of Kumai District Central Kalimantan. The data which is collected to describe the characteristics of the habitat covers the length of the beach, its width, its slope, the distance of the nest with the vegetation, the air humidity, the air temperature, the nest temperature, the moisture content of sand substrate, the texture of sand substrate, the water salinity, and other factors that threaten the hawksbill turtle egg-laying place habitat. From the location of the study, it was found that the length of the beach that becomes the egg-laying place is 5000 meters and 1200 meters that do not become the egg-laying place, the beach width is about 3 – 12 meters at the highest tide and 9 – 20 meters at the lowest tide, the slope of the beach where the nest is found ranges from 10 to 15% and 8 – 11% where the nest cannot be found, the nest distance with the vegetation is about 0 – 2 meters, the air humidity is around 94,7% - 68,8%, the air temperature is about 28,830C - 330C, the nest temperature is about 28,620C, the sand substrate texture is medium with 0,21 – 0,50 µm, and the sea water salinity is 27,5%. At the location of the study there was found that every hawksbill turtle nest located in a shade of sea pandan trees (Pandanus tectorius). Hawksbill turtles are threatened by predators such as monitor lizards (Varanus salvator), ghost crabs (Ocypoda sp), fishing activities, waste bins, and natural factors such as coastal abrasion and the presence of weeds growing on the beach surface. Keyword: Habitat Characteristics, Hawksbill turtle, Tanjung Keluang Natural Park